Bridging the policy gap of Koperasi Desa/Kelurahan Merah Putih (KDMP): from national design to village level practices - Auradian Marta; Raja Muhammad Amin; Rury Febrina; Sofyan Hadi; Margina Ferlan; Meris Essio Mento (Department of Government Studies, Universitas Muhammadiyah Makassar, 2026)
This study examines the policy implementation gap between the national design of KDMP program and its implementation at regional and village levels, particularly in Riau Province. Using an exploratory qualitative approach, data were collected through literature review, focus group discussions, and in-depth interviews with key stakeholders. The analysis applies a gap analysis framework across five dimensions: policy content and context, institutional capacity, stakeholder participation, stakeholder roles and interests, and collaboration and digital governance. The findings reveal a significant discrepancy between rapid legal establishment and limited operational readiness. Although 1,866 KDMP units have been formally established in Riau, only a small proportion are operational in terms of business activation, financing access, and partnerships. This study contributes by developing a multilevel governance framework to explain how national policy design, local institutional capacity, and multi-actor collaboration shape policy outcomes. Strengthening institutional capacity, regulatory alignment, and collaborative networks is essential for ensuring the effectiveness of KDMP as a driver of inclusive rural development.